2009
DOI: 10.1111/j.1447-0756.2008.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of gestational diabetes mellitus by continuing metformin therapy throughout pregnancy in women with polycystic ovary syndrome

Abstract: In PCOS use of metformin throughout pregnancy is associated with and might be responsible for a ninefold reduction (30-3.44%) of gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
68
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 32 publications
(78 reference statements)
5
68
2
1
Order By: Relevance
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Although not all GDM events can be prevented, lifestyle interventions introduced early in pregnancy or before pregnancy have the potential of preventing GDM development, at least among some women. This is supported by the promising findings from large observational studies on pre-pregnancy diet and lifestyle (Table 1), aforementioned positive findings from studies that started the intervention early in pregnancy [31][32][33][34][35][36][37][38][39][40], and by the successful prevention of type 2 diabetes with diet and lifestyle modification among non-pregnant individuals, for example, in the FDPS [26] and in the US DPP [27]. Finally, findings from animal and human medical studies have demonstrated the biological plausibility of improving insulin sensitivity and secretion through diet and lifestyle modification.…”
supporting
confidence: 68%
“…Across the individual intervention studies, large variations exist in multiple aspects of the study design, including GDM diagnostic criteria, duration and timing of the intervention, as well as characteristics of the study population, including their race/ethnicity and GDM risk profile. For example, some studies were conducted among a high-risk population, such as overweight or obese women [32] or on women with polycystic ovary syndrome [31], whereas other study populations included both obese and non-obese women [46]. The intervention approaches themselves were diverse, ranging from yoga, aerobic exercises or resistance training, to targeting different aspects of the diet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 25 trials included for this review, there were four randomised controlled trials (RCTs) [10][11][12][13], one clinical trial [14], four retrospective cohort studies [15][16][17][18], and sixteen prospective cohort studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. These studies were conducted globally with a large number originating from USA.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin was limited to the first trimester in four trials [11,14,16,27], with the remainder continuing metformin for the entire duration of pregnancy. A comparison of continuing metformin in the first trimester and throughout pregnancy was made in four trials [10,23,26,33]. Metformin was used for fertility treatment in most participants prior to pregnancy.…”
Section: Resultsmentioning
confidence: 99%